Genotype-by-environment interaction and stability analyses of grain yield in pigeonpea [Cajanus cajan (L.) Millspaugh]. (3rd April 2021) - Yohane, Esnart Nyirenda; Shimelis, Hussein; Laing, Mark; Mathew, Isack; Shayanowako, Admire
ABSTRACT: Genotype-by-environment interaction (GEI) analysis is fundamental in crop improvement programmes to guide selection and for recommendation of high performing and stable genotypes for breeding or production. The objectives of this study were to quantify the GEI effects and determine grain yield stability among diverse pigeonpea genotypes to select candidate lines for breeding in Malawi. Eighty-one pigeonpea genotypes were tested under six environments using a 9 × 9 alpha-lattice design with two replications. Data collected were subjected to additive main effects and multiplicative interaction (AMMI) analysis and genotype plus genotype-by-environment interaction (GGE) biplot analysis. Genotype, environment, and genotype × environment interaction (GEI) accounted for 16.4, 33.5, and 49.6%, respectively, of the total variation for grain yield. The test environments were delineated into three mega-environments, based on site and seasonal variability. The AMMI and GGE analyses indicated that the top-yielding and stable genotypes across the test environments were MWPLR 24, ICEAP 01155, MWPLR 14, TZA 5582, and MWPLR 4. The selected genotypes are recommended as parental lines for grain yield improvement in Malawi or similar agro-ecologies.